Designing complex socio-technical process systems – the airport example. Issue 5 (22nd November 2018) - Mazhar, Samia; Wu, Paul Pao-Yen; Rosemann, Michael
Abstract : Purpose: A configurable reference model can be used to assist in the development and management of business processes in complex, multi-stakeholder environments. The purpose of this paper is to demonstrate a process design in such environments via configurable process reference modelling, using airports as an example. Design/methodology/approach: Existing reference modelling methods around process modelling, merging and configuration are extended to include contextual and spatial factors using the design science methodology. The approach is empirically based on a set of business process management notation (BPMN) models for international passenger departures, consolidated from five Australian airport case studies via document analysis, interviews and observation. Findings: The use of contextual factors and operational scenarios, structured using the proposed approach, facilitated efficient cross-organisational comparison for configuring processes to suit the needs of a target organisation. The resulting configurable model integrates the perspectives of organisational stakeholder groups with that of the customer in a transparent and unambiguous graphical representation. It is a reusable tool with low data collection needs for each use. Research limitations/implications: Future research should include: version management; how to keep the model current; configurability via modelling objects other than gateways; and cross-discipline application (e.g. as a foundation for quantitative decision-making models). Originality/value: This is the first reported application of configurable reference modelling to airport passenger facilitation. Methodological contributions include the addition of space-sensitive process elements and notation to BPMN; guidelines for systematically deriving contextual factors associated with process variants across similar organisations; and overall normative guidelines for inductively developing a configurable process reference model.